Supernaturalism In Samuel Taylor Coleridge's Major Poems - Ali, Nur Baiti; Efriza, Doni (Jurnal Humaniora Teknologi, 2020)
Samuel taylor coleridgeâ€™s the ancient mariner and kubla khan are the major poems regarded as the greatest compositions in the field of supernaturalism. As a poet of supernaturalism, coleridge strictly eschewed crudeness from his writings. Based on the purpose of this study, that is to seek supernaturalism in samuel taylor coleridgeâ€™s major poems, the research design of this study is conducted by applying content analysis as proposed by koul (1984). Content analysis is concerned with the phenomenon, elements and comparison. Because of its concern, content analysis is sometimes referred to as â€˜documentary activityâ€™ or â€˜information analysisâ€™. The data of this study belong to the non â€“manipulated variables as they are not the result of experiment; these are called the qualitative type. Therefore, the data analyzed with the qualitative descriptive approach. This research will show the nature of the situation as it exists at the time of the study as stated by gay (1987: 189), â€œdescriptive research determines and reports the way the things areâ€. Dream, suggestiveness and vision are the elements of the supernaturalism in these poems which are presented in the research result.